Confirmation of Alleles Inheritance in F1 Progenies Derived from a Cross of Calcutta-4 (Musa acuminata ssp. burmannicoides) and Musa acuminata ssp. microcarpa Based on SSR Markers - Dea Rosalia; Puji Lestari; Andy Soegianto; Darmawan Saptadi; Agus Sutanto; Kristianto Nugroho; Rerenstradika T. Terryana; I Made Tasma; Ika Roostika (Jurnal AgroBiogen, 2020)
Banana breeding to produce improved varieties with disease resistance haracters and other desired traits could sustain its yield. Alleles harbored by parents could be passed on to the offsprings through hybridization, but need to be confirmed using molecular markers. This study aimed to confirm allele inheritance in F1 progenies derived from a cross of Calcutta-4 (Musa acuminata ssp.  burmannicoides) and M. acuminata ssp. microcarpa based on SSR markers. Eleven pairs of SSR primers were used to amplify DNA of 44 progenies using the PCR technique. The results showed that six SSR markers (MaSSR 1.1, MaSSR5.1, MaSSR 6.1, MaSSR 7.1, MaSSR 8.1, and MaSSR 11.1) were polymorphic in both parents. Four markers (MaSSR 1.1, MaSSR 5.1, MaSSR 6.1, and MaSSR 8.1) had PIC >0.7, indicating their informativeness to distinguish these progenies and other genetic studies of banana germplasms. A total of 44 F1 individuals were confirmed to harbor alleles inherited from their parents,suggesting as true progenies from the cross of Calcutta-4 and M. acuminata ssp. microcarpa. This population demonstrated 100% success of hybridization performed. Chi-Square analysis revealed that segregation of all markers did not match to Mendelian ratio 1:2:1, except for MaSSR 1.1 (x2 = 5,62) and MaSSR 6.1 (x2 = 3,77) markers. The genetic traceability of banana F1 progenies demonstrating the usefulness and feasibility of SSR markers in this study provided information on selection of true progenies which may be valuable for breeders to assist selection process in future banana breeding program in Indonesia.